Cohort profile: The Singapore Breast Cancer Cohort (SGBCC), a multi-center breast cancer cohort for evaluation of phenotypic risk factors and genetic markers - Ho, Peh Joo (PUBLIC LIBRARY SCIENCE, 2021)
10.1371/journal.pone.0250102